Inherent uncertainty in the extraction of frequencies from time-domain signals. Issue 3 (5th November 2019) - O'Higgins, Connor; Hester, David; Ao, Wai Kei; McGetrick, Patrick; Robinson, Des
Abstract : One structural health monitoring method used to detect the occurrence of structural damage is the tracking of a structure's natural frequencies. However, for bridges, this is complicated by the changing environmental and operational conditions, which also have an effect on the natural frequencies. Consequently, much of the research effort has been on trying to develop data-modelling approaches that correct for, or remove, environmental effects so that changes in structural behaviour can be revealed. However, the fact that the process of extracting frequencies from bridge response data sets has in itself some inherent uncertainties that have been largely ignored forms the major interest of this study. In this paper, various methods for extracting frequency data from time-domain signals are reviewed, and their suitability for use in automated approaches is discussed. A selection of these methods was then used to obtain frequencies from continuous acceleration data from a bridge over a 20 d period. Comparisons were then made between the obtained frequencies, and any observed differences are highlighted between the methods.